2017
DOI: 10.31223/osf.io/xmj2w
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The stratigraphic record and processes of turbidity current transformation across deep-marine lobes

Abstract: Sedimentary facies in the distal parts of deep-marine lobes can diverge significantly from those predicted by classical turbidite models, and sedimentological processes in these environments are poorly understood. This gap may be bridged using outcrop studies and theoretical models. In the Skoorsteenberg Fm., a downstream transition from thickly-bedded turbidite sandstones to argillaceous, internally layered hybrid beds is observed. The hybrid beds have a characteristic stratigraphic and spatial distribution, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
128
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(130 citation statements)
references
References 0 publications
2
128
0
Order By: Relevance
“…It is interesting to contrast these results with recent work on “hybrid flows” of Kane et al . [], who use the turbulence collapse criterion of Eggenhuisen et al . [] to identify a threshold in a submarine fan (the Skoorsteenberg Formation) beyond which both debris flow or bedload deposits and turbidites are both present.…”
Section: Role Of Knapp‐bagnold Collapsementioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to contrast these results with recent work on “hybrid flows” of Kane et al . [], who use the turbulence collapse criterion of Eggenhuisen et al . [] to identify a threshold in a submarine fan (the Skoorsteenberg Formation) beyond which both debris flow or bedload deposits and turbidites are both present.…”
Section: Role Of Knapp‐bagnold Collapsementioning
confidence: 99%
“…While the results of Kane et al . [] are suggestive, we believe that it is premature to interpret any particular stratigraphic observations using our two‐layer flow hypothesis at this time.…”
Section: Role Of Knapp‐bagnold Collapsementioning
confidence: 99%
“…Many published models seek to explain the close association of turbidite, transitional flow deposit and debrite emplaced as part of the same event (Haughton et al ., ; Talling et al ., ; Kane & Pontén, ; Kane et al ., ). Experiments involving deceleration of clay‐laden flows in the laboratory have shown that it is possible to segregate basal sand from the suspension before the onset of cohesion and en masse deposition of sand and clay together to form the remainder of the bed (Baas et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…() in the Gottero Sandstone. In particular, the occurrence of slurry beds in Log 4 can be related to the deceleration of mud‐rich turbulent flows against the Pievepelago high which, through the increase in fallout rate and consequent turbulence suppression, tend to favour the development of mud‐rich slurries (bed type 6‐4) (see Barker et al ., ; Sumner et al ., ; Baas et al ., ; Tinterri et al ., ; Kane et al ., ).…”
Section: Discussionmentioning
confidence: 97%